Statistical Convergence in Paranorm Sense on Time Scales - Gulsen, Tuba; Koyunbakan, Hikmet; Yilmaz, Emrah; Altin, Yavuz (Chiang Mai Univ, Fac Science, 2022)
In this study, we define statistical convergence and lambda-statistical convergence in paranorm sense on an arbitrary time scale equipped with paranorm. Furthermore, we study on strongly lambda(p)-summability on time scales in paranorm sense. Eventually, some inclusion theorems are proved.
Keywords: time scales; paranorm; statistical convergence